Logistics Implications of Future Changes in Grocery Retailing - Walters, David (Cranfield School of Management, 1982)
This report is a synthesis of views and reactions to the previously reported Delphi exercise. Because it is a synthesis of a number of views its approach is, of necessity, general. The report examines the likely implications of forecast changes of specific aspects of retailing. In addition to the Delphi forecast, statistical data from Government and other sources is introduced to expand and increase the usefulness of the exercise.